Cutibacterium acnes endocarditis: a multicenter case series. (3rd October 2022) - Heinen, F J; Arregle, F; Van Den Brink, F S; Ajmone Marsan, N; Bernts, L H P; Kamp, O; Roescher, N; Verkaik, N J; Roos-Hesselink, J W; Post, M C; Habib, G; Tanis, W
Abstract: Background: Infective endocarditis (IE) due to Cutibacterium acnes (C. acnes) (formerly known as Propionibacterium acnes) is challenging to diagnose. It is suggested that patients often present without fever nor inflammatory parameters. Meanwhile, cardiac abscesses and valve dysfunction are often reported, with a high percentage of patients requiring cardiac surgery [1–7]. No study has yet confirmed the atypical presentation of IE caused by C. acnes. Purpose: To study clinical characteristics and outcomes of patients with C. acnes IE. Methods: A multinational retrospective case series was conducted. Patients who were diagnosed with definite IE according to the modified Duke criteria between 2010 and 2020 were included. There were six participating hospitals. Cases were identified by positive blood cultures or positive valve/prosthesis cultures. Clinical data was retrieved from medical records. Results: We identified 61 cases of C. acnes IE. Patients were predominantly male (n=58, 95%) and had previous cardiac surgery (n=56, 91.8%), which in most cases consisted of aortic valve replacement or Bentall procedures (n=34, 60.7% and n=13, 23.2% respectively). The median time between index surgery and presentation was 31 months (IQR 15.9–69.3). At presentation, fever was absent in 59% of patients (n=36). Most patients experienced symptoms for one to two weeks prior to hospital presentation (41%). At presentation, the median CRP level was 35.5 mg/L (IQR 10.0–70.8). Moreover, in 23% of patients (n=14), the median CRP level was not elevated (<10.0 mg/L). The median leucocyte count at presentation was 9.8x10 9 /L (IQR 8.0–12.3), and thus not exceeding the upper limit of the normal range (10.0x10 9 /L). Approximately half of the blood cultures became positive. In addition, the median time to positivity of blood cultures was seven days (IQR 6–9) and 82.4% of patients had a time to positivity of more than five days. (Redo) surgery was performed in 40 patients (65.5%). Peroperatively, valve dehiscence was observed in 19 patients (47.5%) and vegetations and abscesses were present in 16 patients (40%). The 30-day and one-year mortality rates were 4.9% and 11.5% respectively. Eight patients experienced relapse IE during follow-up of which seven initially received conservative treatment. Conclusion: IE due to C. acnes predominantly concerns males with prosthetic heart valves. The diagnostic process in C. acnes IE is difficult due to its atypical presentation, with frequent absence of fever and inflammatory parameters. Meanwhile, blood cultures remain negative in approximately half of the patients. Moreover, the time to positivity of blood cultures is one week, which further delays the diagnostic process. Redo surgery is required in a high percentage of patients. Funding Acknowledgement: Type of funding sources: None.